Thickness characteristics and improved surface adhesion of a polypyrrole actuator by analysis of polymerization process - Ryu, J.; Jung, S.; Lee, S.-K.; Kim, B. (KOREAN SOC MECHANICAL ENGINEERS, 2005)
Characterizing electrochemical polymerization of polypyrrole film on a substrate depends on many parameters. Among them, potential difference and cumulative charges play important role. The level of potential difference affects the quality of the polypyrrole. On the contrary, cumulative charge affects the thickness of the polypyrrole. The substrate surface is adjusted physically and chemically by treating with sandblasting and the addition of thiol for surface adhesion improvement. Experimental results show that the sandblasted and thiol treated substrate provides better adhesion than non-sandblasted and non-thiol treated substrate.